A young testicular microenvironment protects Leydig cells against age‐related dysfunction in a mouse model of premature aging. Issue 1 (6th August 2018) - Curley, Michael; Milne, Laura; Smith, Sarah; J⊘rgensen, Anne; Frederiksen, Hanne; Hadoke, Patrick; Potter, Paul; Smith, Lee B.
ABSTRACT: Testicular Leydig cells (LCs) are the primary source of circulating androgen in men. As men age, circulating androgen levels decline. However, whether reduced LC steroidogenesis results from specific effects of aging within LCs or reflects degenerative alterations to the wider supporting microenvironment is unclear; inability to separate intrinsic LC aging from that of the testicular microenvironment in vivo has made this question difficult to address. To resolve this, we generated novel mouse models of premature aging, driven by CDGSH iron sulfur domain 2 ( Cisd2 ) deletion, to separate the effects of cell intrinsic aging from extrinsic effects of aging on LC function. At 6 mo of age, constitutive Cisd2 ‐deficient mice display signs of premature aging, including testicular atrophy, reduced LC and Sertoli cell (SC) number, decreased circulating testosterone, increased luteinizing hormone/testosterone ratio, and decreased expression of steroidogenic mRNAs, appropriately modeling primary testicular dysfunction observed in aging men. However, mice with Cisd2 deletion (and thus premature aging) restricted to either LCs or SCs were protected against testicular degeneration, demonstrating that age‐related LCs dysfunction cannot be explained by intrinsic aging within either the LC or SC lineages alone. We conclude that age‐related LC dysfunction is largely driven by aging of the supporting testicular microenvironment.—Curley, M., Milne, L., Smith, S., J⊘rgensen, A., Frederiksen, H., Hadoke, P., Potter, P., Smith, L. B. A Young testicular microenvironment protects Leydig cells against age‐related dysfunction in a mouse model of premature aging. FASEB J. 33, 978–995 (2019). www.fasebj.org